Global burden associated with rare infectious diseases of poverty in 2021: findings from the Global Burden of Disease Study 2021 - Yujia Bao; Yongxuan Li; Yibin Zhou; Ne Qiang; Tianyun Li; Yuzheng Zhang; Marc K. C. Chong; Shi Zhao; Xiaobei Deng; Xiaoxi Zhang; Lefei Han; Jinjun Ran (BMC, 2024)
Abstract Background Rare infectious diseases of poverty (rIDPs) involve more than hundreds of tropical diseases, which dominantly affect people living in impoverished and marginalized regions and fail to be prioritized in the global health agenda. The neglect of rIDPs could impede the progress toward sustainable development. This study aimed to estimate the disease burden of rIDPs in 2021, which would be pivotal for setting intervention priorities and mobilizing resources globally. Methods Leveraging data from the Global Burden of Disease Study 2021, the study reported both numbers and age-standardized rates of prevalence, mortality, disability-adjusted life-years (DALYs), years lived with disability, and years of life lost of rIDPs with corresponding 95% uncertainty intervals (UIs) at global, regional, and national levels. The temporal trends between 1990 and 2021 were assessed by the joinpoint regression analysis. A Bayesian age-period-cohort model was used to project the disease burden for 2050. Results In 2021, there were 103.76 million (95% UI: 102.13, 105.44 million) global population suffered from rIDPs with an age-standardized DALY rate of 58.44 per 100,000 population (95% UI: 42.92, 77.26 per 100,000 population). From 1990 to 2021, the age-standardized DALY rates showed an average annual percentage change of − 0.16% (95% confidence interval: − 0.22, − 0.11%). Higher age-standardized DALY rates were dominated in sub-Saharan Africa (126.35 per 100,000 population, 95% UI: 91.04, 161.73 per 100,000 population), South Asia (80.80 per 100,000 population, 95% UI: 57.31, 114.10 per 100,000 population), and countries with a low socio-demographic index. There was age heterogeneity in the DALY rates of rIDPs, with the population aged under 15 years being the most predominant. Females aged 15-49 years had four-times higher age-standardized DALY rates of rIDPs than males in the same age. The projections indicated a slight reduction in the disease burden of rIDPs by 2050. Conclusions There has been a slight reduction in the disease burden of rIDPs over the past three decades. Given that rIDPs mainly affect populations in impoverished regions, targeted health strategies and resource allocation are in great demand for these populations to further control rIDPs and end poverty in all its forms everywhere. Graphical Abstract